"Mal muß man sich die Hände dreckig machen, dann muß man sie sich eben waschen." Friedrich Zimmermann, 1962 anläßlich der FIBAG-Affäre - Staeck, Klaus; Staeck, Klaus; Steidl, Göttingen (1982)
Bemerkungen: Archivstempel